Response to national policy imperatives for nursing education: a Western Cape case study - F.M. Daniels (AOSIS, 2010)
Since South Africa became a democratic country in 1994, the higher education sector has been faced with the challenge of transformation and restructuring. The Minister of Education in the Education White Paper 3 stated that "the higher education system must be transformed to redress the past inequities, to serve a new social order, to meet pressing national needs and to respond to realities and opportunities" (Department of Education, 1997:2). Higher education institutions were faced with the realities of impending mergers and collaborations across programmes and between universities and technikons. The Council on Higher Education (CHE) submitted a report to the Minister of Education in February 2002 which proposed the establishment of new institutional and organizational forms within regions (Department of Education, 2002: 7-8). The Minister announced changes in higher education based on his assessment of the proposals submitted by the CHE which resulted in the reduction of the number of higher education institutions from 3 6 to 21 (Department of Education, 2002:11-20). There were specific implications for nursing education in the Western Cape. In December 2002 the Minister of Education, Kader Asmal announced that with effect from 2005, the University of the Western Cape (UWC) and a new institution, the Cape Peninsula University of Technology (CPUT) would be the only enrolling institutions for undergraduate nursing education in the Western Cape. The Cape Higher Education Consortium (CHEC) instead proposed the establishment of a common teaching platform for nursing education in the region to meet the objectives of national and provincial government and to make optimal use of the combined strengths of the three universities and the technikon. This proposal was accepted by the minister and the common teaching platform, a unique form of collaboration, was established in 2005.